Investigation of vibration characteristics of cracked aluminum plates repaired with carbon fiber composite patches - Sen, Murat (Sage Publications Ltd, 2025)
The aim of this study was to examine the alterations in the dynamic properties of damaged aluminum plates following repair with carbon fiber composite patches. Initially, cracks of varying lengths (10, 20, 30, 40, and 50 mm) were introduced at different locations (mid-straight, mid-diagonal, corner-straight, and corner-diagonal) on 1.8 x 200 x 200 mm aluminum plates. Subsequently, these induced defects were repaired using single-sided and double-sided patches produced via the vacuum infusion method. The research then focused on analyzing how the resonance frequencies, vibration mode shapes, and damping ratios of the plates changed after these repairs. The dynamic properties of the plates were determined using the Experimental Modal Analysis (EMA) method. The results indicate significant changes in the dynamic properties of the plates due to crack formation and patch repairs. The first five modes of the plates were analyzed, and variations in resonance frequencies, influenced by crack length, location (middle or corner regions), and application type (single-sided or double-sided), reached up to 6.07%. While no substantial change was observed in the vibration mode shapes, particularly at lower frequencies, the fifth vibration mode showed the highest variation at 8.8%. Additionally, remarkably high changes in vibration damping ratios, up to 37.39%, were observed. The findings were presented in a comparative and elucidative manner, aiming to contribute to the literature.
Keywords: Composite patch repair; dynamic analysis; modal analysis; resonance frequency; vibration mode shape; damping ratio